Geodetic Mass Balances and Area Changes of Echaurren Norte Glacier (Central Andes, Chile) between 1955 and 2015 - Farias-Barahona, David; Vivero, Sebastian; Casassa, Gino; Schaefer, Marius; Burger, Flavia; Seehaus, Thorsten; Iribarren-Anacona, Pablo; Escobar, Fernando; Braun, Matthias H. (My University, 2019)
The Echaurren Norte Glacier is a reference glacier for the World Glacier Monitoring Service (WGMS) network and has the longest time series of glacier mass balance data in the Southern Hemisphere. The data has been obtained by the direct glaciological method since 1975. In this study, we calculated glacier area changes using satellite images and historical aerial photographs, as well as geodetic mass balances for different periods between 1955 and 2015 for the Echaurren Norte Glacier in the Central Andes of Chile. Over this period, this glacier lost 65% of its original area and disaggregated into two ice bodies in the late 1990s. The geodetic mass balances were calculated by differencing digital elevation models derived from several sources. The results indicated a mean cumulative glacier wide mass loss of -40.64 +/- 5.19 m w.e. (-0.68 +/- 0.09 m w.e. a(-1)). Within this overall downwasting trend, a positive mass balance of 0.54 +/- 0.40 m w.e. a(-1) was detected for the period 2000-2009. These estimates agree with the results obtained with the glaciological method during the same time span. Highly negative mass change rates were found from 2010 onwards, with -1.20 +/- 0.09 m w.e. a(-1) during an unprecedented drought in Central Andes of Chile. The observed area and the elevation changes indicate that the Echaurren Norte Glacier may disappear in the coming years if negative mass balance rates prevail.
Keywords: glacier mass balance; geodetic method; lidar; central andes; glacier mapping; mountain glacier